Iron deficiency anemia and its effect on HbA1c levels in patients above 30 years - SUMIT CHANDRA KANOJIA,; SWATI SINGH,; ADREENA MITTAL,; ANISH PATEL,; HINA KAUSAR, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Iron deficiency contributes 50% of the anemic burden worldwide. Glycated hemoglobin (HbA1c) is an irreversible product formed due to slow non-enzymatic catalysis of the β-chain of matured hemoglobin (Hb). The glycemic status of the patients with diabetes is monitored through HbA1c for the three months period. IDA is associated with blood loss, hemolysis, hemoglobinopathies, red cell abnormalities, and myelodysplastic disease. IDA also can elevate the turnover of red blood cells, which can increase the glycation of hemoglobin and lead to higher HbA1c concentrations. Aim: To establish a relationship between the levels of HbA1c And Iron Deficiency Anemia. Methods: Total 5ml of Venous blood was collected from patients above 30 years under aseptic conditions and distributed in EDTA and plain vial for serum. Blood samples from participants were sampled in 10ml Vacutainer tubes (Becton Dickinson, Franklin Lakes, NJ) containing EDTA and plain tubes (Becton Dickinson) for hematological analysis and serum separation respectively. The plain vial serum was used for estimation of serum ferritin levels. Complete Blood Count (CBC) and HbA1c estimation were performed using the EDTA samples. Biochemical analyses were performed by Sysmex-350 five-part auto analyzer. Results were systematically entered into a master chart in which were also cross referenced to clinical and other pertinent patient data. The data was then analyzed statistically for interpretation. Results: There was a statistically significant difference when comparing hemoglobin (Hb) levels and mean corpuscular volume (MCV) between the control and study groups. Before treatment, every subject in the study group had Hb ≤13.0 g/dL (p13.0 g/dL. In this study, by the end of treatment in the study group, hemoglobin values showed a statistically significant increase where the percent of patients with hemoglobin >13.0 g/dL was found in 10% and basal mean hemoglobin value of patients was detected to be improved from 6.82±0.32g/dL to 12.66±0.42 (p90%, comparable to controls, indicating adequate resolution of iron deficiency anemia (p<0.001). Conclusion: The evidence shows that iron supplementation has a strong beneficial effect on hemoglobin levels and reverses microcytic anemia in patients with anemia. All subjects in the study group showed low level of Hb and microcytic hypochromic mild anemia suggesting iron deficiency anemia before treatment. Significant uptick of Hb and MCV values on intervention —a quintessential hematological response. This emphasizes the need for early detection and proper treatment of anemia to bring back normal hematological parameters to improve general health. Keywords: Anemia, IDA, Glycated Hemoglobin, microcytic, iron deficiency